Regulation of cosmetic safety in the United States - karstadt, Myra L. (European Journal of Oncology and Environmental Health, 2010)
Cosmetic products are very lightly regulated in the United States, even though cosmetic products may contain hazardous ingredients, including carcinogens. Cosmetic products associated with carcinogenic constituents include hair dyes and, in the past, hair sprays. Gaps in the basic law that controls cosmetics safety- the Federal Food, Drug and Cosmetic Act (FFDCA) are in large part responsible for the Food and Drug Administration (FDA) failing to act on behalf of consumers who use cosmetics.